TELAAH KRITIS TERHADAP HADIS MISOGINIS - Syamsul Hadi Untung; Achmad Idris (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
One aspect that was criticized by liberal feminists in Islam is the hadith of Prophet Muhammad PBUH. This group accused some hadith of Prophet Muhammad PBUH anti to women. They call it misogynistic hadith. Surprisingly, the first pioneer of this discourse is a Muslim woman named Fatima Mernissi. In her book Women and Islam: An Historical and Theological Enquiry, Mernissi has written two sub-chapters examinedthe hadith assumed as misogynistic. This discourse became a serious debate among Muslim scholars. In Islam, fighting for justice and equality for women should be based on the al-Quran and al-Sunnah, so that when one of the sources questioned will rise the restlessness among Muslims. This article tries to study and examine Mernissi’s statement and study about hadiths of the Prophet Muhammad PBUH which described as  misogynistic hadith. This needs to be done, so get the correct meaning and wisdom related to the Prophetic traditions.